Pursue A Masters in ICT at AeU - New, Straits Times (New Straits Times, 2014)
AeU has designed its master course to produce professionals who can manage ICT systems in their organisation and understand the needs of society in which they do business with. - Prof Dr Syed Malek Fakar Duani